Idea obcego w dziele Paula Ricoeura - Amherdt, Franęois-Xavier (Humanistyka i Przyrodoznawstwo, 2018)
The idea of „stranger” is strictly connected with Paul Ricoeur’s life and ethical dimension of his work. Ricoeur experienced the feeling of alienation himself because he spent many years teaching in Chicago. Alienation was a result of separating himself from the Paris society concentrated on philosophical thought dominated by the concept of structuralism and existentialist philosopher, Sartre. In the text a “stranger” is perceived as a hospitable and generous person. Ricoeur refers to biblical tradition and to the works of E. Levinas. Comparing with Levinas’ concept of a “stranger”, he is not a radical reverse, but someone very similar to “I”. Accepting a “stranger” has its socio-political consequences. Sticking to realism he escapes the risk of ideological confinement or the utopian concept of Kant’s everlasting peace.